Application of JavaScript Code Similarity Detection for Assessment of Web Programming Assignment - Muhammad Niswar (EPI International Journal of Engineering, 2022)
Students tend to copy programming assignments from their classmates in programming courses. Students copy codes in various ways, such as changing variable names and code structure order. Lecturers spend much time checking programming assignments, especially when the number of students enrolled in the course is large. They must check whether students have completed their programming assignments individually or copied their classmates' assignments. We developed a JavaScript code similarity detection application for web programming coursework using lexical analysis and Jero Winkler's Algorithm. Our application can detect the level of the students’ programming assignment similarity and assist the lecturer in deciding on plagiarism.